THE INTERNALIZATION OF ANTI-TABARRUJ VALUES IN ISLAMIC EDUCATION: A STUDY OF THE PERSPECTIVES OF USTADZ ADI HIDAYAT AND BUYA YAHYA - Satra, Alihan; Yunika; Khasanah, Kharismatun; Lutfiyyah; Nursyahrani, Reka Juwarni (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study aims to examine and compare the views of Ustadz Adi Hidayat and Buya Yahya regarding the concept of tabarruj from an Islamic perspective, and to explore how their preaching approaches contribute to character education for Muslim women in Islamic educational settings. This is a descriptive qualitative study utilizing primary data from sermon videos and transcripts, and secondary data from books, scholarly journals, and interpretations of relevant Qur'anic verses and Hadiths. Data collection methods include indirect observation and documentation. The findings reveal that both Ustadz Adi Hidayat and Buya Yahya strongly assert that tabarruj is prohibited in Islam as it contradicts values of modesty and honor. They both highlight the importance of cultivating modesty (al-ḥayā’) and manners as part of the moral foundation for Muslim women's character development in the digital age. These insights provide valuable implications for integrating Islamic values into character education in both formal and informal educational environments. Penelitian ini bertujuan untuk mengkaji dan membandingkan pandangan Ustadz Adi Hidayat dan Buya Yahya mengenai konsep tabarruj dalam perspektif Islam serta mengeksplorasi bagaimana pendekatan dakwah keduanya dapat berkontribusi dalam pembentukan karakter Muslimah melalui pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan sumber data primer berupa video ceramah dan transkrip, serta data sekunder dari buku, jurnal ilmiah, dan tafsir ayat-ayat Al-Qur'an serta Hadis yang relevan. Teknik pengumpulan data dilakukan melalui observasi tidak langsung dan dokumentasi. Hasil penelitian menunjukkan bahwa baik Ustadz Adi Hidayat maupun Buya Yahya menekankan bahwa tabarruj merupakan perilaku yang dilarang dalam Islam karena bertentangan dengan nilai kesopanan dan kehormatan. Keduanya menyoroti pentingnya pendidikan rasa malu (al-ḥayā’) dan adab dalam membentuk karakter perempuan Muslim di era digital. Temuan ini memberikan implikasi penting bagi pengembangan pendidikan karakter berbasis nilai Islam dalam kurikulum pendidikan formal dan informal.